Вариабельность отношения стабильных изотопов углерода в пыльце лиственных пород древесных видов в зависимости от погодных условий сезона вегетации - Бляхарчук Татьяна Артемьевна; Симонова Галина Владимировна; Ветрова Ольга Викторовна; Blyakharchuk, Tatyana Artemievna; Simonova, Galina Vladimirovna; Vetrova, Olga Viktorovna (Томский политехнический университет, 2015)
Актуальность работы обусловлена необходимостью поиска более точных маркеров индикации палеоклимата Сибири для верификации стратиграфии отложений при разведке георесурсов. Цель работы. Выявить перспективы использования изотопного состава d13С пыльцы лиственных древесных видов флоры Сибири для палеоклиматических исследований. Методы исследования. С этой целью был исследован изотопный состав пыльцы восьми видов сибирской флоры, собранной в разные годы, и результаты сопоставлены с погодными условиями апреля и мая года сбора пыльцы. Для исследования сухая очищенная пыльца выбранных видов растений сжигалась в окислительно-восстановительном реакторе элементного анализатора Flash 2000. Выделившийся при горении СО2 анализировался в изотопном масс-спектрометре DELTA V Advantage (Том ЦКП СО РАН). Метеоданные для апреля и мая года сбора пыльцы были взяты с интернет-сайта. Результаты. Анализ изотопного состава пыльцы лиственных деревьев сибирской флоры показал перспективность использования этого метода для индикации доминирующих погодных условий периода формирования пыльцы, то есть для палеоклиматических исследований. Исследование показало прямую зависимость обилия стабильного изотопа 13С в пыльце лиственных деревьев от температуры (чем выше температура, тем больше ассимилируется изотопа 13С в пыльце) и обратную зависимость от обилия осадков (чем больше осадков, тем меньше ассимилируется изотопа 13С в пыльце). Ослабленные растения и растения, произрастающие при меньшей солнечной освещенности, ассимилировали заметно меньшее количество изотопа 13С по сравнению со здоровыми растениями, произрастающими в более благоприятных условиях.

The relevance of the discussed issue is caused by the need to find more robust markers of paleoclimatic change in natural archives (peat, sapropel and mineral sediments) for paleogeographic research in Siberian region, which can be used for verification of stratigraphic structure of sediments during exploration of geological resources. The main aim of the study: to reveal the prospects of use of stable carbon isotope 13С detected in pollen of deciduous tree species of Siberian flora for paleoclimatic investigations. The methods used in the study: for this aim the amount of stable carbon isotope 13С was detected in pollen of eight tree species from deciduous clade collected in different years and compared with weather condition of spring time during year of pollen collection. Dry cleaned pollen of selected tree species was burned in redox reactor of element analyzer Flash 2000. CO2 emitted during combustion was analyzed in isotope mass spectrometer DELTA Advantage in Tom CCU SB RAS. The results of stable isotope measurements were compared later with average month temperatures of April and May mentioned for year when pollen was collected. The results. The authors found that content of stable carbon isotope 13С in pollen of deciduous trees of Siberian flora is a perspective indicator of weather conditions during pollen maturation and hence for paleoclimatic research. The investigation showed straight dependence of amount of stable carbon isotope 13С in pollen of deciduous trees on temperature (higher the temperature in period of maturation of pollen is, more 13С isotope was accumulated by plants) and reverse dependence on amount of precipitation (more precipitation was during maturation of pollen, less carbon isotope 13С was accumulated by plants). Weakened plants and plants growing under less sunlight conditions accumulated notably less amount of stable carbon isotope 13С in comparison with healthy plants growing in more favorable environments.
Variability of content of stable isotopes of carbon in pollen of deciduous tree species depending on weather conditions of vegetative season
Keywords: пыльца; древесные виды; стабильные изотопы; углерод-13; стабильные изотопы; фракционирование; температура; осадки; палеоклимат; pollen; tree species; carbon stable isotope 13С; isotopic fractionation of stable isotopes; temperature; precipitation; paleoclimate